Domestic violence and suicide behavior: Women descriptions of violence and its effects - Morfín López, Teresita; Sánchez-Loyo, Luis Miguel (Acta Universitaria, 2015)
The domestic violence has been associated to suicide behavior in female victims. However, the subjective dimension of this association has been slightly studied. The aim of this work was to identify situations of domestic violence in adult female suicide attempters and the emotional state associated to the violence. 20 female suicide attempters participated. A semi-structured interview was applied to each participant. Findings were organized as follows: descriptions of domestic violence; relation between violence and suicide attempt; duty of helping others in family nevertheless her emotional state; internalized violence; isolation and emptiness as the emotions associated with suicide and violence; suicide as solutions to domestic violence. The association between suicide and domestic violence are sustained in family and gender values and beliefs. Females may be emotionally damaged by these cultural values.